2023
DOI: 10.1371/journal.pone.0282688
|View full text |Cite
|
Sign up to set email alerts
|

Co-administration of AYUSH 64 as an adjunct to standard of care in mild and moderate COVID-19: A randomized, controlled, multicentric clinical trial

Abstract: Objective Evaluate the efficacy of AYUSH 64, a standard polyherbal Ayurvedic drug in COVID-19. Methods During the first pandemic wave, 140 consenting and eligible hospitalized adult participants with mild-moderate symptomatic disease (specific standard RT-PCR assay positive) were selected as per a convenience sample, and randomized (1:1 ratio) to an open-label (assessor blind) two-arm multicentric drug trial; standard of care (SOC as per Indian guidelines) versus AYUSH 64 combined with SOC (AYUSH plus). Part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…When used with SOC, Ayush-64 accelerated recovery, decreased hospital stays, and enhanced health in COVID-19 patients. It was deemed secure and well-absorbed [40] .…”
Section: Other Studiesmentioning
confidence: 99%
“…When used with SOC, Ayush-64 accelerated recovery, decreased hospital stays, and enhanced health in COVID-19 patients. It was deemed secure and well-absorbed [40] .…”
Section: Other Studiesmentioning
confidence: 99%
“…5 Ayush-64, an Ayurvedic formulation used to treat malaria, has been repurposed as an adjuvant treatment for mild to moderate COVID-19. 7 Anu Taila, a traditional Ayurvedic compound used for intranasal administration, demonstrated preventive potential with strong antiviral effectiveness, viral load decrease, and virus entry barrier. 8 In a randomized controlled multicenter clinical trial, Withania somnifera ( Ashwagandha ) was found to be more effective and safer than hydroxychloroquine for COVID-19 prevention.…”
Section: Introductionmentioning
confidence: 99%
“…Further it has been repurposed for the management of COVID-19 and has shown to be a significantly effective and safe adjunct in the treatment of mild and moderate COVID-19 in a prospective and randomized controlled drug trial. AYUSH 64 hastened clinical recovery, reduced hospitalization period, and showed early persistent health benefits with minimal/absent drug-related side effects ( Chopra et al, 2023 ). Incidentally in the large community study, Ayush 64 found to provide good therapeutic care to patients with asymptomatic, mild, and moderate COVID-19 in home isolation too ( Srikanth et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%